Are there major differences in the attitudes and service quality of standard and seasonal employees? An empirical examination and implications for practice. Issue 1 (10th July 2018) - Guillaume, Paul; Sullivan, Sherry E.; Wolff, Hans‐Georg; Forret, Monica
Abstract : Despite the increased use of seasonal employees by organizations, few studies have been completed on the attitudes and service quality of seasonal office workers. Using Lautsch's classification model, we analyzed the organizational context in which the standard and seasonal workers in this study were employed. Hypotheses were developed based upon the organizational analysis and social exchange theory. Results from archival data obtained from a web‐based organizational survey of 205 clerical and professional workers indicated contrary to expectations, standard and seasonal employees did not significantly differ in terms of perceptions of overall job conditions, perceived organizational support (POS), or job engagement. However, seasonal employees did report significantly fewer opportunities to work on challenging tasks, less comfortable physical working conditions, and less job security than the standard workers. As predicted, standard employees reported significantly higher levels of service quality performance than seasonal employees. Additionally, job engagement mediated the relationship between POS and service quality for both the standard and seasonal employees. Implications for managing seasonal employees are discussed.